Précieuses raretés des Indes : de la curiosité exotique au placement financier - Rachel Lauthelier-Mourier (Viatica)
This article underlines the interest of French collectors and investors for objects from the Indian Ocean, as early as the first quarter of the 17th century. Thanks to the network of intermediaries that Fabri de Peiresc structured, he is one of those who have first contributed to develop the interest for Indian curiosities. Whereas nobility and financial circles in Paris favor the Dutch “supply chain” and, in this process, the very criteria for acquiring these exotic objects are changing during the Century: more than exotic curiosities to be displayed in cabinets, which the buyers are looking for are precious materials, particularly valued for their financial liquidity.